Perbedaan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang aktif dan yang tidak aktif berorganisasi - Norlatifah Octavia; Marina Dwi Mayangsari; Dwi Nur Rachmah (Psychology Study Program, Faculty of Medicine, Universitas Lambung Mangkurat, 2014)
Penelitian ini bertujuan untuk (1) mengetahui perbedaan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang aktif dan yang tidak aktif berorganisasi, (2) mengetahui hubungan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang aktif berorganisasi dan (3) mengetahui hubungan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang tidak aktif berorganisasi. Metode dalam penelitian ini menggunakan analisis varian multivariat dan analisis korelasi. Subjek penelitian ini adalah 50 orang mahasiswa yang aktif berorganisasi dan 50 mahasiswa yang tidak aktif berorganisasi di Fakultas Kedokteran Universitas Lambung Mangkurat Banjarbaru dengan menggunakan teknik purposive sampling. Hasil penelitian menunjukkan bahwa ada perbedaan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang aktif dan yang tidak aktif berorganisasi, ada hubungan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang aktif berorganisasi dan ada hubungan prokrastinasi akademik dan kecurangan akademik pada mahasiswa yang tidak aktif berorganisasi. The objectives of this study were to find out (1) the differences in academic procrastination and academic cheating on students who were active and inactive in organizations, (2) the correlation between the academic procrastination and the academic cheating on students who were active in organizations, and (3) the correlation between the academic procrastination and the academic cheating on students who were inactive in organizations. The analysisused in this study were multivariate analysis of variance and correlation analysis of Pearson's product moment . The study subjects were 50 students of Medical Faculty of Lambung Mangkurat University who were active in organizations and 50 students of the same faculty who were inactive in organizations. It employed purposive sampling technique. This study was found out that there were differences in academic procrastination and academic cheating on the students who were active and inactive in organizations, there was a correlation between academic procrastination and academic cheating on the active students, and there was also a correlation between academic procrastination and academic cheating on inactive students.